Hubungan Kadar Lipid Serum dengan Nilai Estimasi Laju Filtrasi Glomerulus pada Penyakit Ginjal Kronik - Senge, Claudia E.; Moeis, Emma Sy.; Sugeng, Cerelia E.C. (e-CliniC, 2017)
Abstract: Chronic kidney disease (CKD) is a health problem in the world and the number of patients continues to increase. The results of health research data base (Riskesdas) in 2013 suggested that the prevalence of CKD in Indonesia amounted to 0.2%. Riskesdas mentioned three provinces with the highest CKD cases in Indonesia, as follows: Central Sulawesi 0.5%, North Sulawesi 0.4%, and Gorontalo 0.4%. Dyslipidemia is characterized by the progressive increase in triglyceride rich lipoproteins (Tg), low density lipoprotein (LDL) and decreased high density lipoprotein (HDL), often associated with CKD and contributes to increased cardiovaskular risk. Various experimental studies also show that lipid abnormalities may aggravate the progression of kidney damage. Glomerular filtration rate (GFR) is one of the examination of kidney function in assessing the function of excretion that calculate the amount of filtrate which can be produced by the glomeruli. Decreased levels of LFG indicates the severity of kidney damage. This study was aimed to determine the relationship between serum lipid levels (total cholesterol, HDL, LDL, Tg) and eLFG in outpatients with CKD at Kidney-Hypertension Polyclinic of Prof Dr. R. D. Kandou Hospital Manado. This was a descriptive analytical study with a cross sectional retrospective design using data of the medical records of patients with CKD at Prof Dr. R. D. Kandou Hospital Manado. The study population was patients with CKD 4, CKD 5 ND, and CKD 5 HD. Samples were patients diagnosed as CKD outpatients at Kidney-Hypertension Polyclinic of Prof Dr. R. D. Kandou Hospital from July 2015 to July 2016. The relationships between the study variables were analyzed with Spearman-rho test. The relationships of the variables were as follows: total cholesterol and eLFG showed the r value of -0.279 (p= 0.039); HDL and eLFG showed the r value of -0.024 (p= 0.863); LDL and eLFG showed the r value of -0.287 (p = 0.034); triglycerides and eLFG showed the r value of 0.293 (p=0.039). Conclusion: There was a significant negative correlation between total cholesterol and LDL with eGFRCKD-EPI, and a significant positive correlation between triglyceride and eGFRCKD-EPI.Keywords: CKD, total cholesterol, HDL, LDL, Tg, eGFRCKD-EPI.Abstrak: Penyakit Ginjal Kronik (PGK) merupakan salah satu masalah kesehatan di dunia, dimana jumlah penderita terus meningkat. Hasil data riset kesehatan dasar (Riskesdas) tahun 2013 mengemukakan bahwa prevalensi PGK di Indonesia sebesar 0,2%. Riskesdas menyebutkan tiga provinsi dengan kasus PGK tertinggi di Indonesia adalah provinsi Sulawesi Tengah 0,5%, Sulawesi Utara 0,4% dan Gorontalo 0,4%. Displidemia ditandai oleh adanya peningkatan lipoprotein kaya trigliserida (Tg), Low Density Lipoprotein (LDL), dan penurunan High Density Lipoprotein (HDL), sering berhubungan dengan PGK dan berkontribusi pada peningkatan resiko kardiovaskular. Laju filtrasi glomerulus (LFG) merupakan salah satu pemeriksaan fungsi ginjal dalam menilai fungsi ekskresi, dengan cara menghitung banyaknya filtrat yang dapat dihasilkan oleh glomerulus. Derajat penurunan kadar LFG menandakan beratnya kerusakan ginjal. Penelitian ini bertuujuan untuk mengetahui hubungan kadar lipid serum (kolesterol total, HDL, LDL, Tg) dengan eLFG pada subyek PGK yang rawat jalan di Poliklinik Ginjal-Hipertensi RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang retrospektif menggunakan data rekam medis pasien PGK di RSUP Prof. Dr. R. D. Kandou Manado. Populasi penelitian ialah pasien PGK 4, PGK 5 ND dan PGK 5 HD. Sampel penelitian ialah pasien dengan diagnosis PGK yang rawat jalan di Poliklinik Ginjal – Hipertensi RSUP Prof. dr. R. D. Kandou Manado pada periode Juli 2015-Juli 2016. Hubungan antara variabel penelitian digunakan uji korelasi Spearmen-rho. Hasil penelitian hubungan kolesterol total dan eLFG mendapatkan nilai r= -0,279 dengan p= 0,039. Untuk hubungan HDL dan eLFG didapatkan nilai r= -0,024 dengan p= 0,863. Untuk hubungan LDL dan eLFG didapatkan nilai r= -0,287 dengan p= 0,034 dan untuk Tg dan eLFG didapatkan nilai r= 0,293. Simpulan: Terdapat hubungan korelasi negatif bermakna antara kolesterol total dan LDL dengan eLFGCKD-EPI serta hubungan korelasi positif bermakna antara trigliserida dengan eLFGCKD-EPI.Kata kunci: penyakit ginjal kronik, kolesterol total, HDL, LDL, Tg , eLFGCKD-EPI